Developing a Survey Tool to Assess Implementation of Evidence-Based Chronic Disease Prevention in Public Health Settings Across Four Countries - Budd, Elizabeth L.; Ying, Xiangji; Stamatakis, Katherine A.; deRuyter, Anna J.; Wang, Zhaoxin; Sung, Pauline; Pettman, Tahna; Armstrong, Rebecca; Reis, Rodrigo; Brownson, Ross C. (Frontiers in Public Health, 2019)
Background: Understanding the contextual factors that influence the dissemination and implementation of evidence-based chronic disease prevention (EBCDP) interventions in public health settings across countries could inform strategies to support the dissemination and implementation of EBCDP interventions globally and more effectively prevent chronic diseases. An assessment tool to use across diverse countries is lacking. This study describes the development and reliability testing of an instrument to assess the stage of dissemination, multi-level contextual factors, and individual and agency characteristics that influence the dissemination and implementation of EBCDP interventions in Australia, Brazil, China, and the United States. Methods: Development of the 26-question survey included, a narrative literature review of extant measures in EBCDP; qualitative interviews with 50 chronic disease prevention practitioners in Australia, Brazil, China, and the United States; review by an expert panel of researchers in EBCDP; and test-retest reliability assessment. Results: A convenience sample of practitioners working in chronic disease prevention in each country completed the survey twice (N=165). Overall, this tool produced good to moderately reliable responses. Generally, reliability of responses was higher among practitioners from Australia and the United States than China and Brazil. Conclusions: Reliability findings inform the adaptation and further development of this tool. Revisions to four questions are recommended before use in China and revisions to two questions before use in Brazil. This instrument can contribute toward an improved understanding of the contextual factors that public health practitioners in Australia, Brazil, China, and the United States face in their daily chronic disease prevention work related to the dissemination and implementation of EBCDP interventions. This understanding is necessary for the creation of multi-level strategies and policies that promote evidence-based decision-making and effective prevention of chronic diseases on a more global scale.